Legal Regulation of Marine Pollution from Coastal Waste in North Jakarta - Asomad Asomad (Jurnal Ilmiah Hukum dan Keadilan, 2026)
Marine pollution in North Jakarta, particularly in Jakarta Bay and the coastal area of Tanjung Priok, has intensified due to increasing volumes of coastal waste, dominated by single-use plastics. This article examines the legal regulation of marine pollution caused by coastal waste in North Jakarta using a normative juridical approach supported by limited empirical data from key locations, including Cilincing Subdistrict, the coastal area of Tanjung Priok, and the local Environmental Agency. The analysis focuses on three main aspects: the sources of marine pollution from coastal waste, the existing legal and policy framework, and the role of public participation in pollution control. Normatively, the right to a good and healthy environment is guaranteed under Article 28H(1) of the 1945 Constitution of the Republic of Indonesia, while state control over natural resources is stipulated in Article 33(3). Sectoral environmental governance is primarily regulated under Law No. 32 of 2009 on Environmental Protection and Management and Presidential Regulation No. 83 of 2018 on Marine Debris Management. The findings indicate that plastic waste is the predominant pollutant in Jakarta Bay, originating mainly from land-based sources such as river discharge, domestic and industrial waste, as well as coastal and marine activities. These findings are consistent with international studies on land-based plastic leakage into the marine environment and evidence of microplastic contamination in marine sediments and biota in Jakarta Bay. Effective legal responses require an integrated approach combining source-based prevention through the 3R principles (reduce, reuse, recycle), administrative law enforcement, upstream watershed management, and strengthened public participation mechanisms, including community-based waste banks. This article recommends accelerating the implementation of Presidential Regulation No. 83 of 2018 through cross-sectoral coordination, stricter monitoring of domestic and industrial waste along rivers discharging into Jakarta Bay, the establishment of measurable provincial targets for marine waste reduction, and the use of economic incentives to expand waste bank initiatives. The study is limited by the scope of empirical data derived from presentation materials, highlighting the need for further quantitative research.